A novel regulated network mediated by downregulation HIF1A-AS2 lncRNA impairs placental angiogenesis by promoting ANGPTL4 expression in preeclampsia - Shu, Lijun; Wang, Cong; Ding, Zhengzheng; Tang, Jianjiao; Zhu, Yuanyuan; Wu, Liuxin; Wang, Zheyue; Zhang, Tingting; Wang, Tianjun; Xu, Yetao; Sun, Lizhou (Frontiers in Cell and Developmental Biology, 2022)
Preeclampsia (PE) is the predominant medical condition leading to maternal and fetal mortality, and the lack of effective treatment increases its risk to the public health. Among the numerous predisposing factors, the ineffectual remodeling of the uterine spiral arteries, which can induce abnormal placental angiogenesis, has been focused to solve the pathogenesis of PE. According to the preceding research results, abnormal expression of long non-coding RNAs (lncRNA)s could be associated with the pathological changes inducing PE. To be more specific, lncRNA HIF1A-AS2 was proposed for its potential to participate in the molecular mechanisms underlying PE. In vitro, in trophoblast cell lines HTR-8/SVneo and human umbilical vein endothelial cells HUVECs, HIF1A-AS2 knockdown inhibited cell proliferation, migration and tube formation. Mechanistically, transcription factor FOXP1 could regulate the expression of HIF1A-AS2. Moreover, a series of assays, including RNA pull down and mass spectrometry, RNA immunoprecipitation and chromatin immunoprecipitation assay, revealed that HIF1A-AS2 interacted with Lamin A/C (LMNA) to inhibit ANGPTL4 expression in trophoblast cells, thus further participating in the progression of PE. Taken together, these findings suggested that further analysis on HIF1A-AS2 could contribute to the development of prospective therapeutic strategy for PE.